Distribution and determinants of COVID-19 seroprevalence in a hard-to-access health district in Mali. - Sekou Oumarou Thera; Mady Cissoko; Jordi Landier; Zoumana Doumbia; Amagoron Mathias Dolo; Siriman Traore; Abdoul Karim Sangare; Ibrahima Berthe; Ismaila Thera; Hadiata Berthe; Elisabeth Sogodogo; Karyn Coulibaly; et al. (PLOS Global Public Health)
In November 2023, three years after the onset of the pandemic, Mali officially recorded 33,160 confirmed COVID-19 cases and 743 related deaths. Tombouctou health district, following Bamako, the capital city, emerged as the second major hotspot with over 532 confirmed cases. However, these figures likely underestimate the true scale of the epidemic due to limited healthcare access and diagnostic capacity. This study aimed to describe the early trajectory of the epidemic, estimate seroprevalence, and identify factors associated with COVID-19 in the Tombouctou health district. A multi-level study was conducted in January 2021. First, the epidemic dynamics in Tombouctou were analyzed, estimating the basic reproduction number (R0) using daily case time series. Additionally, a cross-sectional survey was conducted, involving 419 households and 1102 participants, allowing for seroprevalence estimation by age and gender. A face-to-face questionnaire collected information on living conditions and knowledge, attitudes, behaviors and practices, regarding the epidemic. Factors associated with SARS-CoV-2 seropositivity were determined using generalized additive mixed models (GAMMs), adjusted to the variable under study and the level of analysis. We estimated an R0 of 2.08 [1.46-2.93]. The crude seroprevalence of SARS-CoV-2 was 33.5% (309/923, 95% CI: 30.4% to 36.6%). Living in a household where someone had been diagnosed with COVID-19 [Incidence Rate Ratio (IRR)=5.47; 95% CI (4.51 to 6.64)], traditionally wealth households [IRR = 2.02; 95% CI (1.23-3.33)], modernly wealth households [IRR = 1.33; 95% CI (1.02 - 1.72)], and older age (per year) [Adjusted Odds Ratio (AOR)=1.02 (1.00 to 1.03)] were significantly associated with seropositivity. Our analysis highlighted the active circulation of SARS-CoV-2 in Tombouctou, with higher seroprevalence observed among people from wealth households, as well as older age groups. The findings underscore the need for tailored and targeted approach focusing on specific households, demographics and settings.